Piwi/piRNAs control food intake by promoting neuropeptide F expression in locusts. (5th January 2022) - Wang, Huimin; Jiang, Feng; Liu, Xiang; Liu, Qing; Fu, Yunyun; Li, Ran; Hou, Li; Zhang, Jie; He, Jing; Kang, Le
Abstract: Animal feeding, which directly affects growth and metabolism, is an important physiological process. However, the contribution of PIWI proteins and PIWI‐interacting RNAs (piRNAs) to the regulatory mechanism of animal feeding is unknown. Here, we report a novel function of Piwi and piRNAs in regulating food intake in locusts. Our study shows that the locust can serve as a representative species for determining PIWI function in insects. Knockdown of Piwi1 expression suppresses anabolic processes and reduces food consumption and body weight. The reduction in food intake by knockdown of Piwi1 expression results from decreased expression of neuropeptide NPF1 in a piRNA‐dependent manner. Mechanistically, intronic piRNAs might enhance RNA splicing of NPF1 by preventing hairpin formation at the branch point sites. These results suggest a novel nuclear PIWI/piRNA‐mediated mechanism that controls food intake in the locust nervous system. SYNOPSIS: Piwi/piRNAs promote food intake and NPF1 expression in locusts. piRNAs possibly enhance NPF1 splicing by preventing hairpin formation at the branch point site. The locust can serve as a representative species for determining PIWI function in insects. Knockdown of Piwi1 suppresses anabolic processes and reduces food intake and NPF1 expression in locusts. Food intake regulation via Piwi1 might be mediated by enhanced RNA splicing of NPF1 in a piRNA‐dependent manner. Abstract : Piwi/piRNAs promote food intake and NPF1 expression in locusts. piRNAs possibly enhance NPF1 splicing by preventing hairpin formation at the branch point site.